Nurturing Success: Unleashing Employee Motivation through Leadership, Training, and Job Satisfaction - Raharjo, Itot Bian (Jurnal Informatika Ekonomi Bisnis, 2023)
This study examines the influence of Leadership, Training, and Job Satisfaction on employee motivation within Perusahaan Daerah Air Minum (PDAM) Kediri. The research sample consists of 40 permanent employees from the company's office. Data was collected through surveys and questionnaires, and analyzed using validity and reliability tests, multiple regression analysis, t-tests, and an F-test. The results of the regression analysis demonstrate that Leadership, Training, and Job Satisfaction have a significant positive impact on employee motivation. Individually, each factor was found to significantly influence employee motivation. The coefficient of determination (R2) indicates that these variables explain 66.9% of the variance in work motivation. The findings underscore the importance of effective leadership, well-designed training programs, and fostering job satisfaction in enhancing employee motivation. By focusing on these factors, organizations can create a motivating work environment and improve overall employee engagement and performance. This study contributes to the existing literature by providing insights specific to the context of a drinking water company. The findings offer practical implications for leaders and managers in PDAM Kediri, enabling them to enhance employee motivation and contribute to the company's success. Future research should consider additional variables and broaden the scope to gain a comprehensive understanding of employee motivation in this industry.